PENERAPAN NILAI-NILAI MULTIKULTURAL GUNA MENCEGAH PRAKTEK BULLYING PADA SISWA DI SMA MATARAM - Wahidah, Ananda; ZM, Hamidsyukrie; Syafruddin; Ilyas, Muhammad; Malik, Imam; Amalia, Syifa Miftahul (Jurnal Abdi Insani, 2024)
Bullying is a problematic case in the school environment, and usually this bullying action is carried out by peers, which involves physical and psychological violence. This action occurs because of the urge to achieve and maintain a high social status among peers. The impact of bullying can range from physical to psychological disorders. There are several policies related to anti-bullying, but this cannot minimize the cases that have occurred. Apart from policies, preventive efforts also need to be carried out and implemented to prevent bullying behavior, one of which is through instilling multicultural values ​​in high school students in Mataram City. Therefore, we initiated this empowerment activity through the socialization of multicultural values ​​as a form of preventive effort to minimize bullying among students in high schools. This service activity is carried out through socialization with direct discussions starting with material presentations, questions and answers, discussions and evaluations. The results of the questionnaire before the service was carried out showed that only 31.8% of students in Mataram City high schools knew about bullying, while 68.2% of students did not know the forms of bullying. Regarding understanding of multiculturalism, the percentage of high school students in Mataram City who know about it is only 50.1%, while the remaining 49.9% do not know about multiculturalism. Apart from that, 100% of students at Mataram City High School have never participated in socialization on multicultural values, and as many as 59.1% of students have never participated in socialization related to bullying, while 40.9% of students have participated in socialization regarding bullying prevention. After community service and outreach, students' understanding increased, especially regarding bullying and multiculturalism, apart from that, 83.3% of students already knew and understood the impact of bullying and were very ready to implement multicultural attitudes and values ​​to prevent bullying in the school environment.